CORPORATE GOVERNANCE IN NIGERIA: WHERE WE ARE AND WHAT WE NEED - Ekwere, Nsikan (Business Administration Study Program - Universitas Katolik Parahyangan, 2016)
This paper reviews corporate governance issues in Nigeria from both its regulatory and compliance viewpoints. It explores whether rules and regulations as contained in corporate governance codes can adequately address the issue of poor corporate governance and the resultant business failures. It reviews the existing codes of corporate governance to determine whether the implicit interrelationship which should exist between corporate governance and ethics are clearly articulated. The paper finds that while the Nigerian code of corporate governance contains elements of international best practices as specified in OECD, CACG and IOD documents, a number of peculiar institutional weaknesses hinder the achievement of regulatory and judicial remedies open to stakeholders who are wronged as a result of poor corporate governance. The paper thus advocates for measures that instil high ethical and moral standards in boards and management as panacea to doing what is right as well review some codes.